Diagnosis of Vertical Root Fracture with Cone-Beam Computerized Tomography in Endodontically Treated Teeth: Three Case Reports - Miyagaki, Daniela Cristina; Marion, Jefferson; Ferraz, Caio CÃ©zar Randi (Iranian Endodontic Journal, 2013)
A definitive diagnosis of vertical root fracture (VRF) is often a challenging task for clinicians. This is because two dimensional periapical radiographs are usually unable to detect the fracture line due to the direction of the X-ray beam. This report presents a set of 3 cases of endodontically treated teeth that were diagnosed with VRFs based on findings from clinical, radiographic, and cone-beam computerized tomographic (CBCT) examinations. After extraction, VRFs were confirmed in all cases. The presence of periodontal pockets or other signs which would compromise the correct diagnosis could not be detected in all three cases. Fracture lines were only visible with the aid of CBCT which provided useful information for the diagnosis and management of VRF. However, the clinical and radiographic data should not be discarded, but used in conjunction with CBCT.